2018
DOI: 10.1021/acs.joc.8b01608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Colchicinoids and Allocolchicinoids through Rh(I)-Catalyzed [2+2+2+1] and [2+2+2] Cycloadditions of o-Phenylenetriynes with and without CO

Abstract: The nonbenzenoid aromatics, tropones and tropolones, are found in various natural products such as colchicine and hinokitol, which possess significant biological activities. The traditional methods to construct the tropone skeletons include oxidation of cycloheptatriene and [4+3] cycloadditions. In addition, the total synthesis of colchicine and its analogues requires laborious organic transformations in the formations of 6-7-7 fused-ring systems. Transition metal-catalyzed carbocyclization and cycloaddition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Regarding the mechanism, formation of compounds 9 can be understood through a catalytic cycle analogous to others previously proposed for Rh-catalysed [2 + 2 + 2] cycloaddition of triynes. 17 Given that previous studies revealed that solvent effects attributed to toluene in similar Rh-catalysed [2 + 2 + 2] cycloadditions are minor, solvent effects were not included in the present computational study. The overall process from model triyne 7 to afford the merged symmetrical tetrahydroisoquinoline 9 is exergonic by 118.3 kcal mol −1 , very similar to that calculated for a chiral triyne 6a (Δ G R = −119.43 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the mechanism, formation of compounds 9 can be understood through a catalytic cycle analogous to others previously proposed for Rh-catalysed [2 + 2 + 2] cycloaddition of triynes. 17 Given that previous studies revealed that solvent effects attributed to toluene in similar Rh-catalysed [2 + 2 + 2] cycloadditions are minor, solvent effects were not included in the present computational study. The overall process from model triyne 7 to afford the merged symmetrical tetrahydroisoquinoline 9 is exergonic by 118.3 kcal mol −1 , very similar to that calculated for a chiral triyne 6a (Δ G R = −119.43 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Ojima and co-workers reported rapid access to allocolchicinoid derivatives 123 in good to excellent yields by the [2+2+2] cycloaddition of o -phenylenetriynes 122 using [Rh(COD)Cl] 2 (catalyst) and DPPP (ligand) under microwave conditions (Scheme 50 ). 49 The reaction tolerated various functional groups and heteroatoms to access fused 6-7-6-5 tetracyclic 5,7-dihydrodibenzo[ c , e ]oxepine derivatives in a single step.…”
Section: Transition-metal-catalyzed Approachesmentioning
confidence: 99%
“…The use of oxygen and/or nitrogen in the linkers could be tolerated as well, leading to heterocylic 6‐6‐7‐5 scaffolds. Later on, Ojima and co‐workers disclosed the [2+2+2+1] cycloaddition between o ‐phenylenetriynes and CO to form the 6‐7‐7‐5 fused tetracyclic scaffold of colchicinoids in good yield (Scheme 3, bottom) [9b] …”
Section: Transition‐metal‐catalyzed [2+2+2+1] Cycloaddition Reactionsmentioning
confidence: 99%